The Effect of Nutrition Counseling on Dietary Changes in Pregnant Women in Stunting Areas - Septy Ariani; Nuraliyah Sugianti; Bela Magfiroh (Indonesian Journal of Global Health Research, 2026)
Stunting is a priority nutritional problem in Indonesia and is associated with long-term negative impacts on growth, cognitive abilities, and intellectual development. One of the main factors causing stunting is inadequate nutritional intake during pregnancy. Optimal maternal nutrition requires appropriate dietary practices throughout pregnancy, as maternal knowledge significantly influences the child's nutritional status. However, pregnant women living in stunting-prone areas often have limited understanding of proper nutrition and healthy eating patterns. Lack of education and guidance makes behavioral changes in eating habits more difficult to achieve. Nutrition counseling plays a crucial role in improving knowledge, understanding, and implementation of healthy nutrition in the daily lives of pregnant women. This study aimed to determine the effect of nutrition counseling on changes in maternal dietary patterns. A quantitative approach with a one-group pre-test post-test pre-experimental design was used. The instruments consisted of a Food Frequency Questionnaire (FFQ) and an observation sheet, both of which were validated through content validity testing (CVI 0.86) and reliability testing (Cronbach's Alpha 0.82). Data were analyzed using the Wilcoxon Signed Rank Test to assess changes before and after counseling. The results showed an improvement in dietary patterns after the intervention, with a significant difference between pre-test and post-test scores (p = 0.000). These findings indicate that nutritional counseling effectively improves the dietary practices of pregnant women in stunting areas.